Chappaquiddick [videorecording (DVD)] - Clarke, Jason, 1969-; Mara, Kate, 1983-; Helms, Ed; Gaffigan, Jim (Lionsgate, 2018)
Based on historical events, this suspenseful thriller examines the infamous 1969 death of Mary Jo Kopechne, who drowned after Senator Ted Kennedy drove off a bridge on Chappaquiddick Island, and the moral and legal complexities that play out over the following week.